Pengaruh Peraturan Perjalanan Masa Pandemi Covid-19 terhadap Preferensi Penumpang Maskapai Citilink di Bandara Internasional Ahmad Yani Semarang - Novi Kurnia Hulu (Sci-tech Journal (STJ), 2022)
The purpose of the study was to obtain information about the influence of airline passenger travel regulations during the Covid-19 pandemic on the interest of Citilink Airlines passengers at Ahmad Yani International Airport, Semarang. In this study using quantitative methods. This research was conducted using primary data and secondary data. In analyzing the data the instrument used is the validity test, reliability test, simple linear regression test, t test, coefficient of determination test. The results showed that in this study the travel regulations of airplane passengers during the Covid-19 pandemic had a positive and significant influence on the interest of Citilink airline passengers at Ahmad Yani International Airport, Semarang. The results of the study obtained a determinant value of 0.458 which means that the travel regulations of airplane passengers have an influence of 45.8% on the level of interest of passengers at Ahmad Yani International Airport, Semarang. While 54.2% of passenger interest is influenced by other variables that are not examined by the researchers. Keywords: Travel Regulations, Passenger Interests